Book Review " The Law's Eye, Women's Eye": Gender Legal Literacy and Responsiveness of Indonesian Legal System - Ramadhani, Suci; Mahfuz, Muhammad; Mutia Sari, Dian Aulia; Junaedi, Junaedi (Abdi Masyarakat, 2025)
The Indonesian legal system still contains gender bias embedded in the substance, structure, and culture of law. This community service activity aims to: (1) enhance gender legal literacy among academics, legal practitioners, and the general public through a book review; (2) disseminate empirical findings on gender injustice in the Indonesian legal system; and (3) promote the Mubadalah perspective as an alternative framework in Islamic family law reform. The book review activity of "Mata Hukum, Mata Perempuan" was conducted on November 9, 2025, in North Lombok, involving keynote speakers, the author, and three reviewers from various disciplines. This book integrates legal feminism with the Mubadalah perspective to analyze gender bias in marriage law, the juvenile criminal justice system, child marriage prevention, and women's participation in state administration. The activity results showed high enthusiasm among participants in understanding structural gender injustice in Indonesian law. Discussions generated concrete recommendations for more gender-responsive legal reform, including revision of the Marriage Law, strengthening dual accountability mechanisms in the juvenile justice system, and empowering local customary institutions in preventing child marriage. The Mubadalah perspective proved effective as a bridge for dialogue between feminism and Islam in the context of Indonesian Muslim society.